The Determinants of Relationship Between Marketing Mix Strategy and Drivers of Export Performance in Foreign Markets: An Application on Turkish Clothing Industry - (:unkn) unknown (ELSEVIER SCIENCE BV, 2016)
The aim of this study is to investigate the effects of firm characteristics and marketing mix strategies on export performance. An integrative approach is used in designing the research model. Firm-specific characteristics and external factors as antecedents of export performance are included in the model as existed in the literature. Their effects on marketing mix strategy and export performance are investigated in Turkish clothing-textile industry. Based on competition strategies theory, marketing mix strategy is added into the model and its mediating effect on export performance is studied. Variables in the proposed research model were measured by scales already existed in the literature. A questionnaire form is used both via e-mail or face-to-face interviews for gathering data in the survey. Data were collected from export based Turkish textile firms operating in clothing sector. Empirical results indicate that firm characteristics, environmental characteristics, international experience and international commitment are linked to higher levels export performance in Turkish clothing export firms. Another finding implies that marketing-mix strategy has a mediating effect on the relationship. The findings can be generalized only for that sector and provide export managers with useful insights. Another limitation is the restriction of antecedents of export performance to external environment and firm-specific internal factors like international commitment and experience. This paper demonstrates a value for its sector-specific findings. In the Turkish clothing industry, financial, strategic, and competitive dimensions of export performance has been evaluated. Internal and external antecedents and marketing-mix strategy effects for the sector have also contribution in the field.
Keywords: Export performance; firm characteristics; environmental characteristics; international commitment; international experience; Turkish clothing export sector; ENTREPRENEURIAL ORIENTATION; FIRM; CAPABILITIES; CONSTRUCT; LINKING